Search for disappearing tracks in proton-proton collisions at √s=13 TeV - Sirunyan, A. M. (2020)
A search is presented for long-lived charged particles that decay within the volume of the silicon tracker of the CMS experiment. Such particles can produce events with an isolated track that is missing hits in the outermost layers of the silicon tracker, and is also associated with little energy deposited in the calorimeters and no hits in the muon detectors. The search for events with this “disappearing track” signature is performed in a sample of proton-proton collisions recorded by the CMS experiment at the LHC with a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 101 fb−1recorded in 2017 and 2018. The observation of 48 events is consistent with the estimated background of 47.8+2.7−2.3(stat)±8.1 (syst) events. Upper limits are set on chargino production in the context of an anomaly-mediated supersymmetry breaking model for purely wino and higgsino neutralino scenarios. At 95% confidence level, the first constraint is placed on chargino masses in the higgsino case, excluding below 750 (175) GeV for a lifetime of 3 (0.05) ns. In the wino case, the results of this search are combined with a previous CMS search to produce a result representing the complete LHC data set recorded in 2015–2018, the most stringent constraints to date. At 95% confidence level, chargino masses in the wino case are excluded below 884 (474) GeV for a lifetime of 3 (0.2) ns.